2008
DOI: 10.1021/jp804830a
|View full text |Cite
|
Sign up to set email alerts
|

Developing Random Network Theory for Carbon Nanotube Modified Electrode Voltammetry: Introduction and Application to Estimating the Potential Drop between MWCNT−MWCNT Contacts

Abstract: A theoretical model of carbon nanotube (CNT)-modified electrodes is introduced to explain the observed increase in the effective electroactive area of such electrodes when formed by the casting of CNT films on top of an electrode of finite size. The model proposes that a fraction of the CNTs deposited form a conducting network that extends beyond the electrode area and onto the insulating surround. Critical parameters for this situation to occur are described. The random network of conducting CNTs is described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…17 We speculate that the few size distributions available in the literature [37][38][39][40][41][42][43][44] are not representative of the ones that have been used in the production of the percolating networks in CNT composites. Although a speculation, we feel it is plausible because sonication and, in some preparation procedures, screw extrusion 54 causes a larger skewness toward short lengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 We speculate that the few size distributions available in the literature [37][38][39][40][41][42][43][44] are not representative of the ones that have been used in the production of the percolating networks in CNT composites. Although a speculation, we feel it is plausible because sonication and, in some preparation procedures, screw extrusion 54 causes a larger skewness toward short lengths.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the very few available experimental measurements of the length distribution of CNTs, we choose a Gamma distribution and the related Weibull distribution. [39][40][41][42] A limiting case of both of these distributions is the exponential distribution with a probability density function (PDF) f e (L) = η exp(−ηL), 43,44 for which φ p (η)/φ p (η 0 ) = 1/2, with η 0 = η/2, irrespective of the value of the distribution parameter η that takes the form of the inverse mean length. 45 So, an exponential distribution reduces the PT by a factor of 2 (relative to the equivalent monodisperse case).…”
Section: Realistic Size Distributionsmentioning
confidence: 99%
“…Although indicative of a large contact resistance between the carbon nanotubes and the electrode, the above interpretation is subject to a number of assumptions. Specifically the potential drop between the CNT-CNT contacts 13 and the orientation of the tubes will be influential.…”
Section: Recent Work Focusing On the Electrochemical Response Of Individual Carbon Nanotubes (Cnts)mentioning
confidence: 99%
“…While microspotting, electrodeposition and direct growth enable a more precise localization of CNT on the working electrode, it has been shown that drop casting may further extend the electro-active area by creating a sort of conducting CNT forest in the insulating area surrounding the WE [56]. Also for this reason, we decided to use the drop casting technique in this study.…”
Section: Sensitivity and Detection Limit With Carbon Nanotubesmentioning
confidence: 99%